Sodium ion hybrid supercapacitor electrode material, preparation method and supercapacitor

The two-step method of synthesizing transition metal hydroxyoxide with layered semi-metallic properties is solved, and the problems of low capacity and poor cycle life of sodium ion hybrid capacitor electrode materials are achieved, and the sodium ion supercapacitor with high rate performance and ultra-long cycle life are achieved .

CN119132842APending Publication Date: 2024-12-13DONGFENG MOTOR GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411198454.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing sodium ion hybrid capacitor electrode materials have low capacity, poor conductivity and poor cycle life, making it difficult to meet the demand for high stability and efficient storage of sodium ions.

Method used

The transition metal hydroxyoxide with layered semi-metallic properties was synthesized by two-step method, and transition metal hydroxide was formed by electrochemical constant voltage deposition or alkali reaction precipitation, and electrochemical oxidation or oxidant oxidation was performed at room temperature to produce large The transition metal hydroxyoxide at the layer spacing achieves rapid storage of sodium ions and alleviates the performance attenuation caused by structural collapse.

Benefits of technology

It achieves high rate performance and ultra-long cycle life of sodium ion supercapacitors, good energy storage characteristics and cycle stability of electrode materials, with rate performance up to 2A/g and cycle life up to 15,000 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119132842A_ABST
    Figure CN119132842A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode material of a sodion hybrid supercapacitor, a preparation method and a supercapacitor, and relates to the technical field of sodion energy storage devices, the preparation method of the electrode material comprises the following steps: S1, preparing a transition metal ion solution, the transition metal ions comprise one or more of Co < 2 + >, Mn < 2 + >, Ni < 2 + >, Fe < 2 + >, Fe < 3 + > and V < 4 + >, and the transition metal ions comprise one or more of Co < 2 + >, Mn < 2 + >, Ni < 2 + >, Fe < 2 + >, Fe < 3 + > and V < 4 + >; performing electrochemical constant-pressure deposition or alkali reaction precipitation to obtain corresponding transition metal hydroxides; and S2, in an alkaline liquid environment, performing electrochemical oxidation or oxidizing agent oxidation on the transition metal hydroxide obtained in the step S1 at room temperature to generate a corresponding transition metal oxyhydroxide, namely the electrode material. The transition metal oxyhydroxide with the layered semimetal property is rapidly prepared, rapid storage of sodium ions on an electrode is achieved, and the prepared supercapacitor has the advantages of ultra-long cycle life and excellent rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sodium ion energy storage device, in particular to an electrode material of a sodium ion hybrid supercapacitor, a preparation method and a supercapacitor. Background Art

[0002] With the rapid economic development around the world, technological products are constantly being updated and iterated, so people have higher demands on the quality of electrochemical energy storage devices. Currently, lithium-ion batteries have been widely used in various scenarios of life, but the global shortage of lithium resources has led to high battery costs, so the development of alternative battery systems is urgent. The global reserves of sodium resources are much higher than lithium, and the manufacturing cost is relatively low. In addition, sodium has similar physical and chemical properties to lithium, and the production and manufacturing processes are similar, so it has attracted widespread attention.

[0003] However, due to the relatively large radius of sodium ions, the structure of the main electrode material is severely damaged during the cycle process, so the current sodium ion energy storage devices have low capacity and poor cycle life. Sodium ion hybrid capacitors combine the advantages of sodium ion batteries and sodium ion capacitors, with high power density, high energy density and long cycle life, and are expected to be used in the field of pure electric and hybrid vehicles. However, the electrode materials currently studied still face disadvantages such as low capacity, poor conductivity and poor cycle life. Therefore, the development of highly stable and efficient sodium ion storage electrode materials remains a key challenge facing sodium ion hybrid capacitors.

[0004] Therefore, it is necessary to develop an electrode material and a preparation method for a sodium ion hybrid supercapacitor with simple process, ultra-long cycle life and excellent rate performance. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the above-mentioned background technology and provide an electrode material and a preparation method of a sodium ion hybrid supercapacitor with simple process, ultra-long cycle life and excellent rate performance.

[0006] The technical solution of the present invention is: a method for preparing an electrode material for a sodium ion hybrid supercapacitor, comprising:

[0007] S1, prepare transition metal ion solution, the transition metal ion includes Co 2+ , Mn 2+ 、Ni 2+ , Fe 2+ , Fe 3+ 、V 4+ One or more of the above are subjected to electrochemical constant voltage deposition or precipitation with an alkali to obtain a corresponding transition metal hydroxide;

[0008] S2. Electrochemically oxidizing or oxidizing with an oxidant the transition metal hydroxide obtained in step S1 at room temperature to generate a corresponding transition metal oxyhydroxide, thereby obtaining an electrode material.

[0009] In the above scheme, a two-step method is used to synthesize transition metal hydroxide oxide MOOH with layered semi-metallic properties to achieve rapid storage of sodium ions on the electrode. In addition, the interlayer spacing of this type of material is large, and the layered structure shrinks and expands like breathing during the storage of sodium ions, effectively alleviating the performance degradation caused by structural collapse. This scheme uses a two-step method to first generate MOH and then oxidize it to generate MOOH. The reason is that divalent metal cations are the main elements and are more inclined to generate hydroxides, so this type of material needs to be further oxidized. Compared with the direct one-step method to obtain transition metal hydroxide oxide, the advantage of this scheme is that the optional element types and proportions are more adjustable, and it has more storage sites, which improves storage capacity.

[0010] Preferably, in step S1, the transition metal ion concentration in the transition metal ion solution is 0.05-0.5 mol / L, and the transition metal ion Co 2+ Provided by one or more of the metal salts Co(NO3)2, CoCl2, CoSO4, the transition metal ion Mn 2+ Provided by one or more of the metal salts Mn(NO3)2, MnCl2, MnSO4, the transition metal ion Ni 2+ Provided by one or more of the metal salts Ni(NO3)2, NiCl2, NiSO4, the Fe 2+ Provided by the metal salt FeSO4, the transition metal ion Fe 3+ Provided by one or more of the metal salts Fe(NO3)3, FeCl3, Fe2(SO4)3, the transition metal ion V 4+ Provided by metal salt VCl4.

[0011] Preferably, in step S1, the deposition voltage range is -2V to (-0.5)V, the deposition time is 30-600s, and the deposition substrate is any one of nickel foam, stainless steel, carbon cloth, and carbon paper. The voltage range is -2V to (-0.5)V because negative voltage decomposes the corresponding anions to produce hydroxides, thereby precipitating the corresponding metal hydroxides. The deposition time is 30-600s because the electrodeposition speed is fast, and rapid deposition can be completed within minutes.

[0012] Preferably, in step S1, the alkali is added in the form of an aqueous solution when reacting with the alkali for precipitation, the alkali source is any one of urea, hexamethylenetetramine, sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium carbonate, potassium bicarbonate, lithium hydroxide, ammonia water and ethylenediamine, and the molar ratio of the alkali source to the transition metal ion is 1.5-4:1; the temperature range when reacting with the alkali for precipitation is 25-180°C and the reaction time is 0.5-12h.

[0013] Preferably, in step S2, the transition metal hydroxide obtained by electrodeposition is located on the substrate and can be directly oxidized; the transition metal hydroxide obtained by alkali precipitation is pre-treated and coated on the pole piece and then oxidized, and the pre-treatment includes: preparing the transition metal hydroxide with a conductive agent and a binder into a slurry, coating it on the pole piece, and drying it. The purpose of such operation is to achieve rapid oxidation of the hydroxide and avoid multi-step centrifugal drying. The pole piece material can be aluminum foil or carbon cloth, nickel foam, stainless steel, carbon cloth, carbon paper, etc.

[0014] Furthermore, the transition metal hydroxide, the conductive agent and the binder are prepared into a slurry in a mass ratio of 8:1:1, the conductive agent is specifically Ketjen black or acetylene black, and the binder is specifically 3-15wt% polyvinylidene fluoride PVDF emulsion.

[0015] Preferably, in step S2, the electrolyte solution used for electrochemical oxidation is formed by dissolving any one of sodium hydroxide, potassium hydroxide and lithium hydroxide in water, with a concentration range of 0.5-5 mol / L. The oxidation voltage window range is 0-(0.8-1.5) V, and the oxidation time is 50-500 s. The reason for selecting this window range is that the metal cations in the hydroxide can be irreversibly oxidized to form oxyhydroxides.

[0016] Preferably, in step S2, the oxidant is any one of hydrogen peroxide, sodium peroxide, potassium peroxide, ammonium persulfate, liquid bromine, potassium permanganate, potassium dichromate, sodium perchlorate and chlorine, and the transition metal hydroxide is immersed in an aqueous solution of the oxidant with a concentration of 0.1-1 mol / L for full oxidation, and the oxidation time is controlled at 0.5-24h. The excess oxidant is used to ensure that the transition metal hydroxide is fully oxidized to generate the transition metal hydroxide oxide MOOH.

[0017] The present invention also provides an electrode material for a sodium ion hybrid supercapacitor, which is prepared by any of the above methods for preparing the electrode material for a sodium ion hybrid supercapacitor.

[0018] The present invention also provides a sodium ion hybrid supercapacitor, comprising an electrode sheet covered with the above electrode material, sodium metal, a glass fiber diaphragm group, and a sodium ion electrolyte. The electrode sheet, sodium metal, glass fiber diaphragm group, and sodium ion electrolyte are assembled into a hybrid sodium ion supercapacitor under a vacuum environment.

[0019] Preferably, the sodium ion electrolyte is obtained by dissolving a sodium salt in an organic solvent, the sodium salt is any one of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, and sodium perfluorooctane sulfonate, the organic solvent is any one or more of ethylene carbonate EC, ethyl methyl carbonate EMC, propylene carbonate PC, fluoroethylene carbonate FEC, dimethyl carbonate DMC, diethyl carbonate DEC, and diethylene glycol dimethyl ether DEGDME, and the sodium ion concentration in the sodium ion electrolyte is 1 mol / L.

[0020] The beneficial effects of the present invention are:

[0021] 1. The two-step method is used to prepare the electrode material, which first generates MOH and then oxidizes to generate MOOH. The reason is that divalent metal cations are the main elements and tend to generate hydroxides, so this type of material needs to be further oxidized. Compared with the direct one-step method to obtain transition metal hydroxide oxides, the advantages of this scheme are that the types of optional elements and the proportions are more adjustable, and there are more storage sites, which improves the storage capacity.

[0022] 2. Layered semi-metallic transition metal hydroxide oxides are used as electrode materials to achieve rapid oxidation and storage of sodium ions on the electrode. In addition, the interlayer spacing of this type of material is large (this is because this type of material has a layered structure compared to hydroxides, but the anions in this type of material are expelled during the oxidation process). The layered structure shrinks and expands like breathing during the storage of sodium ions, effectively alleviating the performance degradation caused by structural collapse.

[0023] 3. The electrode material prepared by the present invention has good energy storage characteristics and cycle stability. The sodium ion supercapacitor prepared by using the electrode material has a rate performance of up to 2A / g and a cycle life of up to 15,000 times. Therefore, the electrode material has an ultra-long cycle life and excellent rate performance.

[0024] 4. The electrode material prepared by the present invention is not only suitable for sodium ion supercapacitors, but can also be extended to systems with larger ion radius, such as potassium ion, aluminum ion, calcium ion and other supercapacitors, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Electron microscope image of cobalt ferrohydroxide prepared in Example 2

[0026] Figure 2 Electron microscope image of cobalt oxyhydroxide prepared by bromine oxidation in Example 4

[0027] Figure 3 Schematic diagram of rate performance comparison between the sodium ion supercapacitor prepared in Example 2 and the sodium ion supercapacitor prepared using only cobalt hydroxide nanosheets

[0028] Figure 4Schematic diagram of the cycle performance of sodium ion supercapacitor prepared in Example 2 DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The drugs used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods in the art unless otherwise specified.

[0030] The electrode materials are prepared in the following manner:

[0031] S1, dissolving metal salt in water to prepare transition metal ion solution, transition metal ions include Co 2+ , Mn 2+ 、Ni 2+ , Fe 2+ , Fe 3+ 、V 4+ One or more of the metal salts can be selected from Co(NO3)2, CoCl2, CoSO4, Mn(NO3)2, MnCl2, MnSO4, Ni(NO3)2, NiCl2, NiSO4, FeSO4, Fe(NO3)3, FeCl3, Fe2(SO4)3, and VCl4. Cobalt salts Co(NO3)2, CoCl2, and CoSO4 are used to provide Co 2+ , manganese salts Mn(NO3)2, MnCl2, and MnSO4 are used to provide Mn 2+ , nickel salts Ni(NO3)2, NiCl2, NiSO4 are used to provide Ni 2+ , ferrous salt FeSO4 is used to provide Fe 2+ , iron salts Fe(NO3)3, FeCl3, Fe2(SO4)3 are used to provide Fe 3+ , vanadium salt VCl4 is used to provide V 4+ , the total concentration of transition metal ions in the transition metal ion solution is 0.05-0.5 mol / L;

[0032] The corresponding transition metal hydroxide is obtained by the following electrochemical constant voltage deposition or precipitation with alkali,

[0033] The electrochemical constant voltage deposition is specifically as follows: the voltage range is -2V to (-0.5)V, the deposition time is 30-600s, and the substrate is any one of nickel foam, stainless steel, carbon cloth, and carbon paper;

[0034] The precipitation by reaction with alkali is specifically as follows: the alkali is added in the form of an aqueous solution, the alkali source is any one of urea, hexamethylenetetramine, sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium carbonate, potassium bicarbonate, lithium hydroxide, ammonia water and ethylenediamine, the molar ratio of the alkali source to the transition metal ion is 1.5-4:1, and the concentration of the alkali solution is 0.1-0.5 mol / L; the temperature range for precipitation by reaction with alkali is 25-180°C, and the reaction time is 0.5-12h.

[0035] S2. The transition metal hydroxide obtained by electrodeposition is located on the substrate and can be directly oxidized (i.e., electrochemical oxidation or oxidant oxidation). The transition metal hydroxide obtained by alkali precipitation is pre-treated and coated on the electrode and then oxidized (i.e., electrochemical oxidation or oxidant oxidation). The pretreatment includes: preparing the transition metal hydroxide with a conductive agent and a binder into a slurry, coating it on the electrode, and drying it. This operation makes the transition metal hydroxide adhere to the substrate or the electrode, which is convenient for electrochemical oxidation or oxidant oxidation to generate the corresponding transition metal hydroxide oxide, that is, to obtain the electrode material.

[0036] Electrochemical oxidation is specifically as follows: any one of sodium hydroxide, potassium hydroxide, and lithium hydroxide is dissolved in water to form an electrolyte solution with a concentration range of 0.5-5 mol / L. The oxidation voltage window range is 0-(0.8-1.5) V (i.e., from 0 V to 0.8-1.5 V), and the oxidation time is 50-500 s;

[0037] The oxidant oxidation is specifically: any one of hydrogen peroxide, sodium peroxide, potassium peroxide, ammonium persulfate, liquid bromine, potassium permanganate, potassium dichromate, sodium perchlorate and chlorine is used as an oxidant, and the transition metal hydroxide is immersed in an oxidant aqueous solution with a concentration of 0.1-1 mol / L for full oxidation, and the oxidation time is controlled at 0.5-24h. The excess oxidant is used to ensure that the transition metal hydroxide is fully oxidized to generate the transition metal hydroxide oxide MOOH.

[0038] Example 1

[0039] This embodiment provides a method for preparing an electrode material, the steps are as follows:

[0040] S1. Prepare 200 mL of 0.05 mol / L cobalt nitrate solution, and deposit cobalt hydroxide nanosheet arrays on the surface of carbon cloth (substrate) by electrochemical constant voltage deposition at room temperature with a deposition voltage of -1 V and a deposition time of 100 s;

[0041] S2. The prepared cobalt hydroxide is electrochemically oxidized in a 1M potassium hydroxide solution (electrolyte solution) with an electrochemical oxidation window of 0-1.2V and an oxidation time of 100s. After the oxidation is completed, the cobalt hydroxide oxide is washed and dried to obtain a cobalt hydroxide oxide electrode material.

[0042] This embodiment also provides a method for preparing a supercapacitor using the above cobalt hydroxide oxide electrode material: an electrode sheet covered with an electrode material (in this embodiment, the substrate with the above transition metal hydroxide oxide generated on the surface is directly used as the electrode sheet), sodium metal, a glass fiber diaphragm group, and a sodium ion electrolyte are assembled into a hybrid sodium ion supercapacitor under a vacuum environment, wherein the sodium ion electrolyte is obtained by dissolving a sodium salt in an organic solvent, the concentration of the sodium salt sodium hexafluorophosphate is 1M, and the organic solvent contains 5% by volume of FEC and the remaining 95% by volume is formed by DEC:DMC:EC in a volume ratio of 1:1:1.

[0043] Example 2

[0044] This embodiment provides a method for preparing an electrode material, the steps are as follows:

[0045] S1. Prepare 200 mL of 0.05 mol / L cobalt nitrate and 0.025 mol / L ferrous sulfate solution, and deposit cobalt hydroxide iron nanosheet arrays on the surface of nickel foam (substrate) by room temperature electrochemical constant voltage deposition method with a deposition voltage of -1 V and a deposition time of 200 s.

[0046] S2. The prepared cobalt hydroxide is electrochemically oxidized in a 1M potassium hydroxide solution (electrolyte solution) with an electrochemical oxidation window of 0-1.0V and an oxidation time of 120s. After the oxidation is completed, the cobalt hydroxide iron electrode material is washed and dried to obtain.

[0047] This embodiment also provides a method for preparing a supercapacitor using the above cobalt iron hydroxide electrode material: an electrode sheet covered with an electrode material (in this embodiment, the substrate with the above transition metal hydroxide generated on the surface is directly used as the electrode sheet), sodium metal, a glass fiber diaphragm group, and a sodium ion electrolyte are assembled into a hybrid sodium ion supercapacitor under a vacuum environment, wherein the sodium ion electrolyte is obtained by dissolving a sodium salt in an organic solvent, the concentration of the sodium salt sodium hexafluorophosphate is 1M, and the organic solvent contains 5% by volume of FEC and the remaining 95% by volume is formed by DEC:DMC:EC in a volume ratio of 1:1:1.

[0048] Example 3

[0049] This embodiment provides a method for preparing an electrode material, the steps are as follows:

[0050] S1. Mix 500 mL of 0.2 mol / L cobalt chloride solution and 500 mL of 0.4 mol / L urea solution, stir and react for 6 h in an oil bath at 90° C. to generate a precipitate, and centrifuge and wash to obtain cobalt hydroxide nanosheets.

[0051] S2. The prepared cobalt hydroxide is mixed with a conductive agent (Ketjen black) and a binder (5 wt% PVDF emulsion) in a mass ratio of 8:1:1 to form a slurry, coated on carbon paper, and dried. The slurry is then immersed in an aqueous solution of an oxidant (hydrogen peroxide) at a concentration of 0.2 mol / L at room temperature for full oxidation for 12 h. After the oxidation is completed, the slurry is washed and dried to obtain a cobalt hydroxide oxide material.

[0052] This embodiment also provides a method for preparing a supercapacitor using the above cobalt hydroxide oxide electrode material: an electrode sheet covered with an electrode material (in this embodiment, the electrode sheet with transition metal hydroxide oxide generated on the surface is directly used as the electrode sheet), sodium metal, a glass fiber diaphragm group, and a sodium ion electrolyte are assembled into a hybrid sodium ion supercapacitor under a vacuum environment, wherein the sodium ion electrolyte is obtained by dissolving a sodium salt in an organic solvent, the concentration of the sodium salt sodium hexafluorophosphate is 1M, and the organic solvent contains 5% by volume of FEC and the remaining 95% by volume is formed by DEC:DMC:EC in a volume ratio of 1:1:1.

[0053] Example 4

[0054] This embodiment provides a method for preparing an electrode material, the steps are as follows:

[0055] S1. Mix 500 mL of 0.2 mol / L cobalt chloride solution and 500 mL of 0.4 mol / L urea solution, stir and react for 12 h in an oil bath at 90° C. to generate a precipitate, and then centrifuge and wash to obtain cobalt hydroxide nanosheets.

[0056] S2. The prepared cobalt hydroxide is mixed with a conductive agent (acetylene black) and a binder (5 wt% PVDF emulsion) in a mass ratio of 8:1:1 to form a slurry, coated on a carbon cloth, dried, and immersed in an aqueous solution of an oxidant (liquid bromine) with a concentration of 0.1 mol / L at room temperature for full oxidation for 24 h. After oxidation, it is washed and dried to obtain a hydroxy cobalt oxide material.

[0057] This embodiment also provides a method for preparing a supercapacitor using the above cobalt hydroxide oxide electrode material: an electrode sheet covered with an electrode material (in this embodiment, the electrode sheet with transition metal hydroxide oxide generated on the surface is directly used as the electrode sheet), sodium metal, a glass fiber diaphragm group, and a sodium ion electrolyte are assembled into a hybrid sodium ion supercapacitor under a vacuum environment, wherein the sodium ion electrolyte is obtained by dissolving a sodium salt in an organic solvent, the concentration of the sodium salt sodium hexafluorophosphate is 1M, and the organic solvent contains 5% by volume of FEC and the remaining 95% by volume is formed by DEC:DMC:EC in a volume ratio of 1:1:1.

[0058] Comparative Example 1

[0059] The cobalt iron hydroxide nanosheets obtained in step S1 of Example 2 are directly prepared into a supercapacitor: an electrode sheet covered with an electrode material (in this embodiment, the substrate with cobalt iron hydroxide generated on the surface is directly used as the electrode sheet), sodium metal, a glass fiber diaphragm group, and a sodium ion electrolyte are assembled into a hybrid sodium ion supercapacitor under a vacuum environment, wherein the sodium ion electrolyte is obtained by dissolving a sodium salt in an organic solvent, the concentration of the sodium salt sodium hexafluorophosphate is 1M, and the organic solvent contains 5% by volume of FEC and the remaining 95% by volume is DEC:DMC:EC in a volume ratio of 1:1:1.

[0060] Performance Testing

[0061] The morphology of the cobalt iron oxyhydroxide prepared in Example 2 is as follows Figure 1 As shown. Figure 1 It can be seen that the cobalt iron hydroxide maintains an array structure after oxidation, indicating that the transition metal hydroxide prepared by the present invention has the advantages of stable structure, large specific surface area and sufficient exposure of active sites.

[0062] The morphology of the cobalt iron oxyhydroxide prepared in Example 4 is as follows Figure 2 As shown. Figure 1 It can be seen that the cobalt iron hydroxide maintains a hexagonal flake structure after oxidation, and the surface of the material is cracked to a certain extent after treatment, indicating that the flake thickness of the cobalt hydroxide prepared by this method is too thick. The oxidation process will destroy the surface morphology, but it can still maintain the integrity of the flake structure. The samples with cracked surfaces expose more active sites, which helps to improve the storage capacity.

[0063] The rate performance of Comparative Example 1 and Example 2 was tested by assembling a half-cell with metallic sodium as the negative electrode.

[0064] The results are as follows Figure 3 As shown, from Figure 3 It can be seen that the cycle test is carried out at different current densities, and the maximum current of Example 2 reaches 2A / g.

[0065] from Figure 3 It can be seen from Comparative Example 1 that the cobalt (iron) hydroxide material has no capacity, that is, it cannot reversibly store sodium ions. Figure 3 It can be seen from Example 2 that cobalt (iron) hydroxide oxide has a good capacity at different current densities, and can still show a good capacity retention rate after returning to a small current, indicating that the material prepared by the present invention has the advantages of good conductivity, reversible storage capacity and excellent rate performance.

[0066] The cycle performance of Example 2 was tested by assembling a half-cell with metallic sodium as the negative electrode.

[0067] The results are as follows Figure 4 As shown, from Figure 4 It can be seen from the figure that the initial capacity of the cobalt (iron) hydroxide material in Example 2 is 60 mAh / g at a high current of 2 A / g. After 15,000 cycles, the capacity still maintains more than 80% of the initial value. This shows that the capacitor prepared by the present invention has the advantages of excellent structural stability and cycle stability. Figure 4 It can be seen that the Coulomb efficiency is basically close to 100%, indicating that this type of material has excellent reversible storage performance.

Claims

1. A method for preparing an electrode material for a sodium ion hybrid supercapacitor, characterized in that: include: S1, prepare transition metal ion solution, the transition metal ion includes Co 2+ , Mn 2+ 、Ni 2+ , Fe 2+ , Fe 3+ 、V 4+ One or more of the above are subjected to electrochemical constant voltage deposition or precipitation with an alkali to obtain a corresponding transition metal hydroxide; S2. Electrochemically oxidizing or oxidizing with an oxidant the transition metal hydroxide obtained in step S1 at room temperature to generate a corresponding transition metal oxyhydroxide, thereby obtaining an electrode material.

2. The method for preparing an electrode material for a sodium ion hybrid supercapacitor according to claim 1, characterized in that: In step S1, the transition metal ion concentration in the transition metal ion solution is 0.05-0.5 mol / L, and the transition metal ion Co 2+ Provided by one or more of the metal salts Co(NO3)2, CoCl2, CoSO4, the transition metal ion Mn 2+ Provided by one or more of the metal salts Mn(NO3)2, MnCl2, MnSO4, the transition metal ion Ni 2+ Provided by one or more of the metal salts Ni(NO3)2, NiCl2, NiSO4, the Fe 2+ Provided by the metal salt FeSO4, the transition metal ion Fe 3+ Provided by one or more of the metal salts Fe(NO3)3, FeCl3, Fe2(SO4)3, the transition metal ion V 4+ Provided by metal salt VCl4.

3. The method for preparing an electrode material for a sodium ion hybrid supercapacitor according to claim 1, characterized in that: In step S1, the deposition voltage range is -2V to (-0.5)V, the deposition time is 30-600s, and the deposition substrate is any one of nickel foam, stainless steel, carbon cloth, and carbon paper.

4. The method for preparing an electrode material for a sodium ion hybrid supercapacitor according to claim 1, characterized in that: In step S1, the alkali is added in the form of an aqueous solution when reacting with the alkali for precipitation, the alkali source is any one of urea, hexamethylenetetramine, sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium carbonate, potassium bicarbonate, lithium hydroxide, ammonia water and ethylenediamine, and the molar ratio of the alkali source to the transition metal ion is 1.5-4:1; the temperature range when reacting with the alkali for precipitation is 25-180°C and the reaction time is 0.5-12h.

5. The method for preparing an electrode material for a sodium ion hybrid supercapacitor according to claim 1, characterized in that: In step S2, the transition metal hydroxide obtained by electrodeposition is located on the substrate and can be directly oxidized; the transition metal hydroxide obtained by alkali precipitation is pre-treated and coated on the electrode and then oxidized, and the pre-treatment includes: preparing the transition metal hydroxide with a conductive agent and a binder into a slurry, coating it on the electrode, and drying it.

6. The method for preparing an electrode material for a sodium ion hybrid supercapacitor according to claim 1, characterized in that: The electrolyte solution used for electrochemical oxidation is formed by dissolving any one of sodium hydroxide, potassium hydroxide and lithium hydroxide in water, with a concentration range of 0.5-5 mol / L. The oxidation voltage window range is 0-(0.8-1.5)V, and the oxidation time is 50-500s.

7. The method for preparing an electrode material for a sodium ion hybrid supercapacitor according to claim 1 or 5, characterized in that: In step S2, the oxidant is any one of hydrogen peroxide, sodium peroxide, potassium peroxide, ammonium persulfate, liquid bromine, potassium permanganate, potassium dichromate, sodium perchlorate and chlorine, and the transition metal hydroxide is immersed in an oxidant aqueous solution with a concentration of 0.1-1 mol / L for full oxidation, and the oxidation time is controlled at 0.5-24h.

8. An electrode material for a sodium ion hybrid supercapacitor, characterized in that: The electrode material is prepared by the method for preparing the electrode material of the sodium ion hybrid supercapacitor according to any one of claims 1 to 7.

9. A sodium ion hybrid supercapacitor, characterized in that: It comprises an electrode sheet covered with the electrode material as claimed in claim 8, sodium metal, a glass fiber diaphragm, and a sodium ion electrolyte. The electrode sheet, sodium metal, glass fiber diaphragm group, and sodium ion electrolyte are assembled into a hybrid sodium ion supercapacitor under a vacuum environment.

10. The sodium ion hybrid supercapacitor according to claim 9, characterized in that: The sodium ion electrolyte is obtained by dissolving a sodium salt in an organic solvent, wherein the sodium salt is any one of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, and sodium perfluorooctane sulfonate; the organic solvent is any one or more of ethylene carbonate EC, ethyl methyl carbonate EMC, propylene carbonate PC, fluoroethylene carbonate FEC, dimethyl carbonate DMC, diethyl carbonate DEC, and diethylene glycol dimethyl ether DEGDME; and the sodium ion concentration in the sodium ion electrolyte is 1 mol / L.